Intranigral Administration of β-Sitosterol-β-D-Glucoside Elicits Neurotoxic A1 Astrocyte Reactivity and Chronic Neuroinflammation in the Rat Substantia Nigra - Claudia Luna-Herrera; Irma A. Martínez-Dávila; Luis O. Soto-Rojas; Yazmin M. Flores-Martinez; Manuel A. Fernandez-Parrilla; Jose Ayala-Davila; Bertha A. León-Chavez; Guadalupe Soto-Rodriguez; Victor M. Blanco-Alvarez; Francisco E. Lopez-Salas; Maria E. Gutierrez-Castillo; Bismark Gatica-Garcia; et al. (Journal of Immunology Research)
Chronic consumption of β-sitosterol-β-D-glucoside (BSSG), a neurotoxin contained in cycad seeds, leads to Parkinson’s disease in humans and rodents. Here, we explored whether a single intranigral administration of BSSG triggers neuroinflammation and neurotoxic A1 reactive astrocytes besides dopaminergic neurodegeneration. We injected 6 μg BSSG/1 μL DMSO or vehicle into the left substantia nigra and immunostained with antibodies against tyrosine hydroxylase (TH) together with markers of microglia (OX42), astrocytes (GFAP, S100β, C3), and leukocytes (CD45). We also measured nitric oxide (NO), lipid peroxidation (LPX), and proinflammatory cytokines (TNF-α, IL-1β, IL-6). The Evans blue assay was used to explore the blood-brain barrier (BBB) permeability. We found that BSSG activates NO production on days 15 and 30 and LPX on day 120. Throughout the study, high levels of TNF-α were present in BSSG-treated animals, whereas IL-1β was induced until day 60 and IL-6 until day 30. Immunoreactivity of activated microglia (899.0±80.20%) and reactive astrocytes (651.50±11.28%) progressively increased until day 30 and then decreased to remain 251.2±48.8% (microglia) and 91.02±39.8 (astrocytes) higher over controls on day 120. C3(+) cells were also GFAP and S100β immunoreactive, showing they were neurotoxic A1 reactive astrocytes. BBB remained permeable until day 15 when immune cell infiltration was maximum. TH immunoreactivity progressively declined, reaching 83.6±1.8% reduction on day 120. Our data show that BSSG acute administration causes chronic neuroinflammation mediated by activated microglia, neurotoxic A1 reactive astrocytes, and infiltrated immune cells. The severe neuroinflammation might trigger Parkinson’s disease in BSSG intoxication.